The ESG Dilemma in Indonesia’s Metal & Others Mineral Firms: Evaluating Corporate Social Responsibility and Good Corporate Governance Effects the Financial Performance: Dilema ESG pada Perusahaan Logam & Mineral Lainnya di Indonesia: Evaluasi Dampak Corporate Social Responsibility dan Good Corporate Governance terhadap Kinerja Keuangan. - Thierry Charlson Lohart; Susan Grace V. Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study examines the impact of Corporate Social Responsibility and Good Corporate Governance on Financial Performance in Indonesia's metal and mineral mining sector from 2021 to 2024. Through quantitative analysis of secondary data from eight companies' financial, sustainability, and annual reports, multiple linear regression was employed alongside classical assumption tests and hypothesis testing. Results demonstrate that both variables significantly enhance Financial Performance individually and collectively. The t-test value for Corporate Social Responsibility was 2.258 and Good Corporate Governance was 3.353 surpassed the critical value of 2.0423 at significance levels below 0.05, while the F-test result of 18.450 (p < 0.001) confirmed their combined effect. With an R² of 0.560, these factors explain 56% of performance variance, indicating their substantial influence. The findings highlight how integrating these practices into corporate strategy can improve financial sustainability and risk management, offering valuable insights for corporate leaders and policymakers in promoting sustainable mining operations, while establishing a basis for further research on additional performance determinants.